Integrasi Karakter Religius dan Kearifan Lokal: Model Pembelajaran PAUD Berbasis Tradisi NU di KB Muslimat NU Miftahul Ulum - Wasis Wijayanto; Windi Putri Kurnia Sefiyani; Ravena Zahra Endry (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
The critical need to integrate moderate Aswaja-based religious character with the preservation of Kudus local wisdom as a bulwark against globalization in early childhood education has not yet been widely explored. This study aims to describe the flagship program model and analyze the learning system at Kelompok Bermain (KB) Muslimat NU Miftahul Ulum Loram Kulon, Kudus, in the context of integrating religious character and local wisdom. A descriptive qualitative method was employed with data triangulation through participatory observation, in-depth interviews, and document analysis conducted over one month. The findings show that flagship programs such as the habituation of Sholat Dhuha, memorization of Surat al-Wāqiʿah, Friday ziarah activities, and participation in Ampyang Maulid are effectively internalized through a hidden curriculum based on play-based learning. The main findings include: (1) visualization of spiritual values through consistent daily religious activities; (2) strengthening of cultural identity through active participation in local Kudus traditions; and (3) the formation of moderate character through the principles of Tawassuth, Tawazun, and Tasamuh, which are integrated into every learning activity, with teachers acting as key facilitators who bridge spiritual and cultural values in each learning center. This synergy model produces children’s character outcomes that are religious, moderate, and firmly rooted in local cultural identity, and can be positioned as a best practice for faith-based early childhood education. The study is limited in terms of generalizability because it was conducted in a single institution, has not measured long-term impacts, and assesses character primarily through qualitative-descriptive indicators. Nevertheless, the integration model has a significant impact on shaping children’s identity as “Cah Kudus” with noble character and offers a framework that can be replicated in other PAUD institutions under Nahdlatul Ulama in Indonesia, with adaptation to the local wisdom of each region.